Mind Mapping Model, Student Learning and Creativity: Evidence From Economics Lesson of Senior High School - Nanda, Yovita Fillia (Classroom Action Research Journal (CARJO), 2018)
Student learning outcomes are low due to lack of participation and weak understanding of students on the material delivered. Students have difficulty repeating the material that has been obtained. Student notes are linear and monotonous so students are tired of reading and have difficulty re-learning the notes that have been made. The application of mind mapping learning models is done to overcome the low learning outcomes and creativity of students. The study was conducted with Classroom Action Research and used a qualitative approach. Student learning outcomes and creativity have increased from cycle 1 to cycle 2.